Utilization of Microbial Consortia as Biofertilizers and Biopesticides for the Production of Feasible Agricultural Product - Renganathan Seenivasagan; Olubukola Oluranti Babalola (Biology, 2021)
Farmers are now facing a reduction in agricultural crop yield, due to the infertility of soils and poor farming. The application of chemical fertilizers distresses soil fertility and also human health. Inappropriate use of chemical fertilizer leads to the rapid decline in production levels in most parts of the world, and hence requires the necessary standards of good cultivation practice. Biofertilizers and biopesticides have been used in recent years by farmers worldwide to preserve natural soil conditions. Biofertilizer, a replacement for chemical fertilizer, is cost-effective and prevents environmental contamination to the atmosphere, and is a source of renewable energy. In contrast to chemical fertilizers, biofertilizers are cost-effective and a source of renewable energy that preserves long-term soil fertility. The use of biofertilizers is, therefore, inevitable to increase the earth’s productivity. A low-input scheme is feasible to achieve farm sustainability through the use of biological and organic fertilizers. This study investigates the use of microbial inoculants as biofertilizers to increase crop production.